Penggunaan Media Peta dalam Metode Discovery Learning untuk Meningkatkan Pemahaman Materi Kenampakan Alam Indonesia pada Siswa Kelas V Sekolah Dasar - Syafati Putri Hardiati; Ibnu Muthi (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to examine the effectiveness of using map media in the discovery learning method to improve the understanding of fifth grade elementary school students on the material of natural features of Indonesia. This study is a qualitative study with a library research approach that relies on data sources from scientific and credible literature, such as accredited journals, academic books, and relevant previous research reports. Data were analyzed using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of discovery learning assisted by map media can increase student activity, interest, and involvement in learning. Students become more active in exploring information, discussing, and expressing opinions. In addition, the use of maps as a visual medium encourages an increase in students' cognitive understanding, as indicated by a significant increase in test scores after learning. Interaction between students through group discussions has also proven effective in forming shared understanding and improving social skills, such as cooperation, communication, and tolerance. The discovery learning method encourages meaningful learning because students are directly involved in the process of discovering concepts through learning experiences, not just receiving information from teachers. Changes in student behavior from passive to active show that this approach is in line with the principles of constructivism and supports character development and learning independence in accordance with the Merdeka Curriculum. Thus, discovery learning assisted by map media is an effective, participatory, and contextual learning strategy in improving the quality of social studies learning in elementary schools.